THE GENERAL COMPOSITION OF FINANCIAL INTERMEDIARIES. BANKS. THEIR MAIN FUNCTIONS - Xodjimamedov A.A,; Sayfiddinova Shaxzoda Najmiddin qizi, (TADQIQOTLAR, 2026)
ABSTRACT This article examines the general composition of financial intermediaries, with a  specific  focus  on  banks  and  their  main  functions  within  the  financial  system. Financial intermediaries play a critical role in mobilizing savings and allocating capital efficiently  across  the  economy.  Banks,  as  the  primary  financial  intermediaries, facilitate economic growth by providing essential services such as deposit acceptance, credit  provision,  and  payment  processing.  The  study  explores  the  structural components of financial intermediaries and analyzes how banks operate to support economic stability and development.